Mobile Multicast Sender Support in Proxy Mobile IPv6 (PMIPv6) Domains - Thomas Schmidt and Shuai Gao and Hong-Ke Zhang and Matthias Wählisch (2014)
Multicast communication can be enabled in Proxy Mobile IPv6 (PMIPv6) domains via the Local Mobility Anchors by deploying Multicast Listener Discovery (MLD) proxy functions at Mobile Access Gateways, by using direct traffic distribution within an ISP's access network, or by selective route optimization schemes. This document describes a base solution and an experimental protocol to support mobile multicast senders in PMIPv6 domains for all three scenarios. Protocol optimizations for synchronizing PMIPv6 with PIM, as well as a peering function for MLD proxies are defined. Mobile sources always remain agnostic of multicast mobility operations.